Thromboembolic Disease in Patients with Metastatic Femoral Lesions: A Comparison Between Prophylactic Fixation and Fracture Fixation. (15th February 2017) - Aneja, Arun; Jiang, Jimmy J.; Cohen-Rosenblum, Anna; Luu, Hue L.; Peabody, Terrance D.; Attar, Samer; Luo, T. David; Haydon, Rex C.
Abstract : Background: We are not aware of any previous studies that have compared the rate of venous thromboembolic events in patients who underwent prophylactic intramedullary nailing because of an impending fracture with the rate in patients who underwent intramedullary nailing after a pathological fracture. The objective of the present study was to determine if the rate of venous thromboembolic events varies between patients who are managed with prophylactic fixation and those who are managed with fixation after a pathological fracture. Methods: We performed a retrospective comparative study in which the Nationwide Inpatient Sample database was used to identify all patients who had undergone femoral stabilization, either for a pathological femoral fracture or for prophylactic fixation of femoral metastatic lesion, over a period of 10 consecutive years (between 2002 and 2011) in the United States. Demographic data, comorbidities, venous thromboembolic event rates, and other common postoperative complications were compared between the 2 groups. Results: Patients who were managed with prophylactic fixation had significantly higher rates of pulmonary embolism (p < 0.001; adjusted odds ratio, 2.1) and deep-vein thrombosis (p = 0.03; adjusted odds ratio, 1.5). Patients who were managed with fixation after a pathological fracture had a significantly greater need for blood transfusion, higher rates of postoperative urinary tract infection, and a decreased likelihood of being discharged to home (p < 0.001 for all). Conclusions: Patients with metastatic disease who undergo prophylactic intramedullary nailing have higher observed rates of venous thromboembolic events than those who undergo nailing for the treatment of a pathological fracture and should be actively and vigilantly managed in the postoperative period. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.